Impacts of Court Ruling on Digital Democracy and Free Expression - Ikawati, Linda; Mardani, Retno Eko; Saraya, Sitta; Putra, Rengga Kusuma (PDIH Untag Semarang, 2025)
This study aims, first, to analyze the legal reasoning of the Constitutional Court in Decision Number 115/PUU-XXII/2024, which annulled the phrase